(untitled) (Mustansiria Dental Journal, 2018)
Conventional tooth the presence of interdental papillae in the maxillary anterior region plays a key esthetic role. The presence or absence of the interproximal papilla is of great concern to periodontists, orthodontists, restorative dentists and to patients The aim of the study was to determine the association between different distances and central papilla recession The central papilla was visually assessed in 50 adults students of age ranged between (19-25 years) in dental clinic, then by using standardized periapical radiographs for the maxillary central incisors, the following vertical distances were measured: papilla tip to contact point (PT-CP), bone crest to contact point (BC-CP), proximal cementoenamel junction to contact point (pCEJ-CP), bone crest to papilla tip BC-PT(the papilla height (PH)).Interdental width (IDW) was measured horizontally. Subjects were divided into 2 groups according to interdental width (IDW) and pCEJ-CP distance respectively: 1. (28) subjects with IDW≤2mm and pCEJ–CP >4 mm as narrow-long group 2. (22) Subjects with IDW≤2mm and pCEJ– CP ≤ 4 mm as narrow-short group. Narrow-long group exhibited more papilla recession, (PT-CP) mean was 2.5mm and the difference was statistically significant. Positive correlations were found between (BC-CP), (pCEJ-CP), (IDW) and central papilla recession and more stronger correlations were found with (BC-CP) (r = 0.856). Papilla height was negatively correlated with (BC-CP), (pCEJ-CP), (IDW) and stronger correlation was found between papilla height and (BC-CP) (r = -0.502) Central papilla recession is associated with narrow interdental width and long pCEJ-CP distance, papilla presence influenced by different distances, some of them are (BC-CP), (pCEJ-CP), (IDW) distances, (BC-CP) had stronger effect on the presence of central papilla.